Travelling images : looking across the borderlands of art, media and photography - Dahlgren, Anna (Rethinking art's histories., 2018)
This book critically examines images in the borderlands of the art world, investigating relations between visual art and vernacular visual culture within different images communities from the 1870s to the present day. It concentrates on the mechanisms of such processes and their implications for the understanding of art and art-historical narratives. Merging perspectives from art history and visual culture studies with media studies, it fills a gap in the field of visual studies through its use of a diversity of images as prime sources. Where textual statements are scarce the book maps visual statements instead, demonstrating the potential of image studies. Consequently, it will be of great relevance to those interested in art and visual culture in modernity, as well as discourses of the notion of art and art history writing.